Expanding the Universe of Hemoplasmas: Multi-Locus Sequencing Reveals Putative Novel Hemoplasmas in Lowland Tapirs (Tapirus terrestris), the Largest Land Mammals in Brazil - Mongruel, Anna Claudia Baumel [UNESP]; Medici, Emília Patrícia; Canena, Ariel da Costa; Calchi, Ana Cláudia [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (MDPI, 2022)
The lowland tapir (Tapirus terrestris) is the largest land mammal in Brazil and classified as a vulnerable species, according to the assessment of the risk of extinction. The present study aimed at investigating the occurrence and genetic diversity of hemoplasmas in free-ranging T. terrestris from the Brazilian Pantanal and Cerrado biomes. Blood samples were collected from 94 living and eight road-killed tapirs, totalizing 125 samples Conventional PCR targeting four different genes (16S rRNA, 23S rRNA, RNAse P, and dnaK) were performed, and the obtained sequences were submitted for phylogenetic, genotype diversity, and distance analyses. The association between hemoplasma positivity and possible risk variables (age, gender, and origin) was assessed. Out of 122 analyzed samples, 41 (41/122; 33.61% CI: 25.84–42.38%) were positive in the 16S rRNA-based PCR assay for hemoplasmas. Positivity for hemoplasmas did not differ between tapirs’ gender and age. Tapirs from Pantanal were 5.64 times more likely to present positive results for hemoplasmas when compared to tapirs sampled in Cerrado. BLASTn, phylogenetic, genotype diversity, and distance analyses performed herein showed that the sampled lowland tapirs might be infected by two genetically distinct hemoplasmas, namely ‘Candidatus Mycoplasma haematoterrestris’ and ‘Candidatus Mycoplasma haematotapirus’. While the former was positioned into “Mycoplasma haemofelis group” and closely related to ‘Candidatus Mycoplasma haematoparvum, the latter was positioned into “Mycoplasma suis group” and closely related to ‘Candidatus Mycoplasma haematobos’. The impact of both putative novel species on tapir health status should be investigated.
Keywords: Cerrado; Hemotropic Mycoplasma; Lowland tapirs; Pantanal